Expression of vitamin D receptor, CYP24A1, and CYP27B1 in normal and inflamed canine pancreases - Lee, Dohee; Kim, Sanggu; Koo, Yoonhoi; Chae, Yeon; Wang, Juwon; Kim, Soochong; Yun, Taesik; Yang, Mhan-Pyo; Kang, Byeong-Teck; Kim, Hakhyun (Frontiers in Veterinary Science, 2023)
Vitamin D plays a role in anti-inflammatory processes, and the alteration of its metabolism is associated with the inflammatory processes of pancreatitis. This study was performed to evaluate the expression of the vitamin D receptor (VDR) and the two major enzymes that regulate vitamin D metabolism, 1α-hydroxylase (CYP27B1) and 24-hydroxylase (CYP24A1), in the canine pancreas and to compare their degrees of immunoreactivity between normal and inflamed pancreases. Five normal and inflamed pancreatic tissues each were obtained from six dogs. The expression of VDR, CYP24A1, and CYP27B1 were determined immunohistochemically, and the degree of immunostaining was assessed semiquantitatively. The VDR was expressed in the ducts, acini, and islets of Langerhans of normal pancreases and in the ducts and acini of inflamed ones. There was a significant difference in the immunoreactivity score for VDR in the islets of Langerhans between normal (median, 3 [interquartile range, 2–7.5] score) and inflamed pancreatic tissues (0 [0–0.5] score, p = 0.03). CYP24A1 was expressed in the ducts and islets of Langerhans in both normal and inflamed pancreases, whereas CYP27B1 was expressed in the ducts and acini in only some normal and inflamed pancreatic tissues. This study showed that VDR expression decreased in inflamed pancreases and demonstrated CYP24A1 and CYP27B1 expression in the canine pancreas for the first time. These findings indicate that the pancreas could regulate the metabolism and biological activity of vitamin D and suggest that a decrease in these might be related to the pathophysiology of pancreatitis.